2017
DOI: 10.1108/srj-05-2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

The effect of equity and bond issues on sustainability disclosure. Family vs non-family Italian firms

Abstract: Purpose\ud This article studies firms’ attitudes to using sustainability reporting in order to facilitate the raising of external capital and the effect of the ultimate controlling owner on disclosure. \ud Design/methodology/approach\ud A disclosure index is constructed on the basis of sustainability reports, for a sample of 230 Italian listed firms. Empirical analysis is based on panel data models. \ud Findings\ud Firms are more prone to disclose when they are planning to issue equity/bonds. Family control do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 77 publications
4
33
0
3
Order By: Relevance
“…Previous studies have highlighted that inflating earnings practices in family firms is driven by the need to facilitate debt management [28]. The less significant relationship between upward earnings management and the extent of CSR suggests that family firms view this type of information as being of less interest for their lenders [112]: they may rely on other signals that are more focused on voluntary financial disclosure, such as earnings forecasts.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have highlighted that inflating earnings practices in family firms is driven by the need to facilitate debt management [28]. The less significant relationship between upward earnings management and the extent of CSR suggests that family firms view this type of information as being of less interest for their lenders [112]: they may rely on other signals that are more focused on voluntary financial disclosure, such as earnings forecasts.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, since this study investigates six board-related factors from three different aspects of board governance, we avoid the problem of focusing narrowly on only one specific board characteristic, hence, minimizing the probability of omitting important variables in our regression analysis. Future research may actually explore even finer contextual delineations, such as family versus non-family firms [48] or other categories of stakeholders beyond shareholders as represented by the boards of directors [49].…”
Section: Discussionmentioning
confidence: 99%
“…Berrone et al [43] continued the research and found that SEW is based on five different dimensions: "(1) Family control and influence; (2) identification of family members with the firm; (3) Binding social ties; (4) Emotional attachment; and (5) Renewal of family bonds to the firm through dynastic succession" (acronym FIBER). Recent studies draw on the socioemotional wealth framework, which effectively points out family firms' motivations and agency conflict peculiarities [44,45].…”
Section: Literature Reviewmentioning
confidence: 99%